Neurochemistry of major depression: a study using magnetic resonance spectroscopy. - Godlewska, B; Near, J; Cowen, P (2015)
RATIONALE: Magnetic resonance spectroscopy (MRS) is an acceptable non-invasive means of studying brain neurochemistry in depression. Previous studies in depressed patients have focused on measurement of the amino acid neurotransmitters, γ-aminobutyric acid (GABA) and glutamate. OBJECTIVES: The aim of this study is to use MRS in conjunction with the ultrashort echo time 'SPECIAL' technique to measure cortical levels of GABA, glutamate and glutathione (GSH) levels in unmedicated patients with major depression. We also examined the effect of 6-week treatment with the selective serotonin re-uptake inhibitor, escitalopram. METHODS: We studied patients with DSM-IV major depression and healthy age-matched controls using proton MRS. GABA, glutamate and GSH were measured relative to creatine in a voxel placed in occipital cortex. RESULTS: There was no difference in GABA or glutamate levels between depressed participants and controls; however, depressed patients had lower GSH levels. Six-week escitalopram treatment, which resulted in significant clinical responses in some patients, did not alter concentrations of GABA, glutamate or GSH. CONCLUSIONS: The sources of variability of GABA and glutamate measures in different studies of depressed patients require further study. Our results suggest that concomitant treatment with selective serotonin re-uptake inhibitors (SSRIs) is unlikely to be an important confounding factor. If lowered GSH levels can be confirmed, they may represent the presence of oxidative stress in some depressed patients.